LA QUEBRANTADA SALUD DEL APÓSTOL - López Pelegrín, Lilian Ramona; Lapinell Frías, Thayli; Betancourt Oliva, Ernesto; Valera Varón, Teresa (Revista 16 de abril, 2017)
The life of José Martí is well known since his revolutionary work; nevertheless, this titanic task rested on a health broken by multiple ailments. Motivated by the incomplete knowledge of the students of the Medical Sciences Branch of Bayamo on the health of Martí, evidenced in the results of an applied survey, the present bibliographical review was made from analytical-synthetic and historical-logical methods with the objective of characterizing the main health problems that afflicted our Apostle. For this, 10 bibliographical sources were consulted which allowed concluding that the health of José Martí was characterized by a visible deterioration due to multiple diseases such as sarcocele, sarcoidosis, chronic catarrhal conjunctivitis with drooping of the right eyelid and frequent headaches, acute broncholaringitis and inguinal adenopathies; In addition, his psychic state was altered by the multiple contradictions and misunderstandings he suffered.